The consequences of Ataturk’s secularization on Turkey - Daud, Ismail; Nooraihan, Ali; Fadzli, Adam (Canadian Center of Science and Education, 2015)
Mustafa Kamal Ataturk was known as one of the important figures responsible in making new modern Turkey. Resulting from his modernization and secularization process, there were several consequences upon Turkish nations in particular that related to social and religious as well as political aspects. This paper discusses some of those consequences in the contexts of modern Turkey. Using a secondary data analysis, published materials written by scholars and writers in the field, the study found that Kemal’s reforms had totally brought a new system of life based on the western style whilst rejecting Islamic tradition and its culture. This includes his policy to terminate the political role of Islam or taking Islam out of politics. Kemal’s modernization could be regarded as one of the main factors for the social and religious changes in modern Turkey.